The co-construction of coherence at episode boundaries in cooperative dialogues - Moccero, María Leticia (Lenguas Modernas, 2012)
The findings informed in this paper are part of an ongoing project on coherence and cohesion in casual conversation, in progress at University of La Plata. In this study we analyze the ‘communicative labour’ done by speakers at transition points between episodes to contribute to the global coherence of the text. We focus on the strategies used by actors to co-construct coherence at episode boundaries (Linell, 1998; Korolija, 1998). The corpus comprises 60 audio or video-recorded dyadic and polyadic conversations among university students aged between 18 and 28, from different universities in Argentina. We agree with Linell (1998) and Korolija (1998) that participants in this kind of interaction –and analysts– assume that both parties cooperate in the process of building coherence. We adopt the concept of episode (Linell, 1998; Korolija, 1998), since it is appropriate for the fragmentation and analysis of the colloquial conversations under study, which consist of both ‘chunks’ and ‘chat’ segments (Eggins & Slade, 1997). The analysis reveals that speakers deploy a variety of strategies –which they combine according to their evaluation of shared knowledge– to offer cues to listeners that will help them establish the inter-episode relationships necessary to make sense of the text.